Environmental education in the curriculum of biological sciences courses: a documentary study (Revista Científica Integrada, 2025)
Objective: To analyze the inclusion of Environmental Education in the curricular matrix and pedagogical project of a Biological Sciences course. Method: Descriptive, exploratory and documentary study, carried out between February and December of 2023, at a Higher Education Institution in the city of Quirinópolis- GO. Based on the analysis of the syllabuses of the disciplines and curricular matrices of the years 2009, 2015 and 2021, qualitative-quantitative analyses were carried out to verify the number of disciplines and topics that refer to environmental themes. Results: The analyses indicate that the Biological Sciences course presents Environmental Education in its pedagogical project, syllabuses and disciplines, however, in a secondary way, since this theme is not, in general, linked to teaching practice, and, when it appears, it is inserted in few areas of knowledge, such as, for example, Ecology, Botany and some pedagogical disciplines, being, therefore, little treated in an interdisciplinary way in this course. Conclusion: It was found that the insertion of the environmental theme occurs insufficiently and in only some disciplines of the course, compromising the individual's formation in relation to Environmental Education.
Keywords: Environmental education; Initial teacher training; Biology curriculum; Educational public policies